Analysis of the Validity of Electronic Evidence in Criminal Trial Proceedings and the Implementation of Its Admissibility (Judgment Study): Analisis Keabsahan Bukti Elektronik dalam Pemeriksaan Persidangan Perkara Pidana dan Implementasi Admisibilitasnya (Studi Putusan) - Vanessa, Vanessa; Firmansyah, Hery (Indonesian Journal of Law and Economics Review, 2025)
General Background: The rapid expansion of digital technology has reshaped evidentiary practices in criminal proceedings, introducing electronic evidence with characteristics distinct from conventional physical proof. Specific Background: Despite the legal recognition of electronic evidence through the ITE Law and its amendments, its vulnerability to manipulation demands strict compliance with formal and material validity requirements, including authentication and digital forensic examination. However, Indonesian courts often differ in implementing these standards. Knowledge Gap: The inconsistency in applying formal requirements—particularly digital forensic authentication—creates uncertainty regarding the admissibility and evidentiary value of electronic evidence. Aims: This study analyzes the legal validity of electronic evidence in criminal trials and examines how admissibility is implemented in practice through case studies of Decisions No. 175/Pid.Sus/2024/PN Jmb and No. 60/Pid.B/2019/PN Drh. Results: Findings show that courts inconsistently apply authentication procedures; some accept electronic evidence without forensic verification, while others rely on comprehensive digital forensic analysis to establish authenticity and integrity. Novelty: This research offers a comparative doctrinal assessment demonstrating how differing implementations of formal and material requirements directly affect evidentiary certainty. Implications: Uniform technical guidelines for digital forensic standards and judicial assessment are essential to ensure legal certainty, safeguard due process, and strengthen the probative value of electronic evidence in Indonesia’s criminal justice system. Highlights: Electronic evidence requires both formal (authenticity, integrity) and material (relevance, reliability) validity to be legally admissible. Courts show inconsistent implementation, with some accepting electronic evidence without forensic authentication. Digital forensics strengthens evidentiary certainty by verifying data integrity and supporting judicial accuracy. Keywords: Electronic Evidence, Digital Forensics, Admissibility, Criminal Procedure, Authentication